Respuesta :
Answer:
(2, 4 )
Step-by-step explanation:
y = 2x → (1)
3x + y = 10 → (2)
substitute y = 2x into (2)
3x + 2x = 10
5x = 10 ( divide both sides by 5 )
x = 2
Substitute x = 2 into (1)
y = 2 × 2 = 4
solution is (2, 4 )
Answer:
x=2 and y=4
Step-by-step explanation:
Let's solve your system by substitution.
y=2x and 3x+y=10
Rewrite equations:
y=2x;3x+y=10
Step: Solvey=2xfor y:
y=2x
Step: Substitute2xforyin3x+y=10:
3x+y=10
3x+2x=10
5x=10(Simplify both sides of the equation)
5x/5=10/5
(Divide both sides by 5)
x=2
Step: Substitute 2 for x in y=2x:
y=2x
y=(2)(2)
y=4 (Simplify both sides of the equation)
answer:x=2 and y=4